Spatial Analysis of Pacu Jawi Cultural Tourism in Tanah Datar District - Anwar, Hairul; Mariya, Sri (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
ABSTRACT: The traditions of a community are often seen as a tourist attraction and used as a regional mainstay. One of the cultural expressions of the agricultural traditions of the Tanah Datar Regency community is Pacu Jawi. This research aims to analyze the spatial aspects of Pacu Jawi cultural tourism in terms of the human geography approach. The research method used is descriptive qualitative with the characteristics of in-depth interviews, holistic perspectives and comprehensive descriptions. Secondary data review was conducted for map analysis of other spatial attributes. The research locus is in four sub-districts, namely Pariangan, Lima Kaum, Sungai Tarab and Rambatan, all of which are within the administrative area of Tanah Datar Regency, West Sumatra Province. The research findings show that the Pacu Jawi tradition as a tourist attraction can maintain social cohesion and cultural sustainability of local communities. The location of Pacu Jawi in Tanah Datar Regency is known as Luhak Nan Tuo (home village) of the Minangkabau people, which shows the primacy of its cultural practices. Road access to the Pacu Jawi location is quite affordable with a choice of various routes with different distances and travel times. Public facilities such as accommodation and health services are available in the Regency Town. Socio-economically, Tanah Datar people mostly work as farmers and the dominant land use for rice fields shows that the Pacu Jawi tradition is still contextual and functional for the community.